Community weight management, obesity prevention and treatment, across the life-course - Avery, Amanda J. (2017)
Obesity results from complex interactions between biological, behavioural, social and environmental factors. The focus of this thesis, both the collection of papers presented and the extended abstract, is on community-based approaches to the prevention and treatment of obesity across five important key life stages. The importance of early life influences, including the intrauterine environment, and the subsequent impact on body fatness across the life-course is discussed. Published research included considers the impact of interventions which aim to limit gestational weight gain on baby’s’ birthweights and the wider influence on sustained breastfeeding. However research presented also suggests that pregnant women receive limited information from healthcare professionals and whilst pregnancy should provide an ideal opportunity for public health intervention, the postnatal period may be more acceptable as a time to provide support and advice. The prevalence of childhood obesity has continued to increase. The most significant predictor of childhood obesity is parental obesity. A paper is presented which demonstrates that engaging adults in lifestyle programmes can have a positive impact on both the diet and activity habits of their family. A systematic review considers how TV viewing during meal-times may influence the foods and drinks consumed with the findings suggesting that the practice of eating whilst watching TV has a negative impact on the diet quality. It is recognised that sugar-sweetened beverages (SSBs) contribute significantly to the free sugar dietary intake, particularly the %total energy intake of children and adolescents. A further published review asks the question, which interventions that aim to reduce the intake of SSBs lead to reduced body fatness in children. There is a need for both primary prevention activities to prevent unhealthy weight gain and interventions to treat overweight and obese children/adolescents. Published data provides evidence for an intervention which does lead to weight loss in obese adolescents, leading to enhanced self-esteem which helps to improve their lifestyles behaviours. Young adulthood represents a period of change with increasing independence. There may be few occasions to discuss weight management with young adults but a presented paper explores the opportunities in primary care. Obesity is associated with a number of chronic diseases, one example being type 2 diabetes which is now presenting in adolescents and young adults. Losing weight can have a significant clinical impact on the glycaemic control of people with diabetes and thus reduce the health burden associated with the condition. Type 2 diabetes is now reversible if significant weight loss is achieved. A paper is presented which evaluates weight management in people with diabetes and the associated impact on glycaemic control. Prevalence data suggests that 25 million adults in the UK are either overweight or obese. Given the health burden to both the individual and society, scalable solutions are required which are delivered in a community setting. Through collaboration with a commercial weight management organisation (CWMO), a series of papers are presented which explore the feasibility and effectiveness of referral from primary care to CWMOs. CWMOs, using behavioural strategies, are well placed to support the large numbers of people who need weight management guidance and a referral scheme may address the health inequalities seen in obesity prevalence. One example of a well-established behavioural strategy, target setting, is considered in more detail with evidence of the importance of target setting presented. As with all research, weight management research is confounded by methodological issues. Community- based programmes are often more complex than clinical trials and contamination may be an issue. The extended abstract explores the methodological issues related to the presented papers in more detail. Whilst we can continue to improve our methodology it is important that we advance our knowledge as to what works to reduce the obesity epidemic. Sadly there will probably not be one solution which is effective at an individual level given the psychosocial complexities of obesity. Ideally we need to promote a nutritionally balanced diet and adequate levels of daily activity which enable children and adults to maintain a healthy weight across the life-course starting at the very beginning of conception.